Comparison of Ultrasound-Guided Local Dexmedetomidine Injection vs. Corticosteroid Injection in the Treatment of Chronic Plantar Fasciitis: A Randomized Clinical Trial - Ghasemi, Mahshid; Taheri, Mehrdad; Nazari, Fatemeh; Khoshooei, Artadokht; Amanollahi, Alireza; Ali Anvari, Hadi (Novelty in Biomedicine, 2023)
Background: Heel pain is commonly caused by chronic plantar fasciitis, associated with pain and activity limitation in patients. Although steroid injection is a popular method to treat this disease, it has side effects and provides short-term pain relief. The study was designed to investigate the effects of dexmedetomidine and corticosteroid injection in treating chronic plantar fasciitis. Materials and Methods: A total of 70 participants were divided into two groups. The intervention group received a mixture of dexmedetomidine (1μg/kg) with 1 ml of lidocaine 2%. The control group received a combination of 1ml of corticosteroid (40mg triamcinolone) with 1ml of lidocaine 2%. Outcome measures were evaluated with Numerical Rating Scale (NRS) and Maryland foot score (MFS) before, one, and three months after the intervention. Results: Significant improvements in NRS and MFS were observed in both groups at 1 and 3 months of follow-up compared to baseline(P<0.001). NRS score improvement in the first month was more significant in the corticosteroid group compared to the dexmedetomidine group. However, after three months, the dexmedetomidine group experienced greater pain reduction (P=0.012) and higher functional ability (P<0.001) than the corticosteroid group. Conclusion: Local injection of dexmedetomidine provided significant and long-term effects on pain severity and physical activity. Corticosteroids caused an immediate but short‑term effect, whereas sustained improvement in the dexmedetomidine group was observed during the follow-up.